Endoscopic Submucosal Dissection for Early Gastric Cancer in Elderly vs. Non-Elderly Patients: A Systematic Review and Meta-Analysis - Zhao, Jiting; Sun, Zhen; Liang, Junwei; Guo, Song; Huang, Di (Frontiers in Oncology, 2022)
Objective: This study aimed to review the applicability and complications rate associated with endoscopic submucosal dissection (ESD) for early gastric cancer in elderly patients. Methods: Databases of PubMed, Embase, CENTRAL, and ScienceDirect were searched till 15th April 2021. All types of studies comparing ESD in the elderly vs non-elderly were included. Subgroup analysis was conducted for the following groups: ≥80 years vs <80 years, ≥75 years vs < 75 years, and ≥65 years vs <65 years. Results: 17 studies were included. Meta-analysis indicated no statistically significant difference in the en-bloc resection rates (OR: 0.92 95% CI: 0.68, 1.26 I2=8% p=0.62) and histological complete resection rates (OR: 0.93 95% CI: 0.75, 1.15 I2=26% p=0.50) between elderly and non-elderly patients. The results were non-significant even on subgroup analysis. Overall, we found a non-significant but a tendency of increased perforation rates in the elderly as compared to non-elderly patients (OR: 1.22 95% CI: 0.99, 1.52 I2=0% p=0.06). However, there was a significantly increased risk of perforation in elderly patients aged ≥80 years as compared to patients <80 years (OR: 1.50 95% CI: 1.00, 2.24 I2=3% p=0.05). Bleeding rates were not different in the two groups (OR: 1.07 95% CI: 0.87, 1.32 I2=19% p=0.52). Pooled analysis indicated a statistically significantly increased risk of pneumonia in elderly patients (OR: 2.52 95% CI: 1.72, 3.70 I2=7% p<0.00001). Length of hospital stay was reported only by five studies. Meta-analysis indicated no significant difference between the two study groups (MD: 0.67 95% CI: -0.14, 1.48 I2=83% p=0.10). Conclusion: En-bloc and histological complete resection rates do not differ between elderly and non-elderly patients undergoing ESD for early gastric cancer. Elderly patients have a small tendency of increased risk of perforation with significantly increased rates in the super-elderly (≥80 years of age). The risk of pneumonia is significantly higher in elderly patients but the rates of bleeding do not differ. The certainty of evidence is “very low” and there is a need for high-quality studies taking into account confounding factors to enhance the quality of evidence.